CEDIP to meet the educational challenges - (:unkn) unknown (My University, 2008)
We believe that we can count on the firmness of ahuman potential that engages in innovation. However, the teacher-researcher set in Gabon as in the DRC and the CongoBrazzaville is getting there, it would have to change the paradigm to get out of theresistance whose causes come from the stagnation of the African schoolcurrent state and failing governance. One of the possibilities to exploreWould be to see to what extent to rely on support opportunitiesoffered in contemporary society. It would be a question, for example, of obtaining, on the one hand, developing bi- and/or multilateral bodies and organizations, viable educational projects and, on the other hand, by opening up to thepopulations of these respective nations who are in the diaspora can together seek and innovate. The crossing of looks, of technologies could be of a considerable contribution. In this perspective, shouldn't this representation of an Africa which while others design and build be over? Examples of self-initiatives starting from a department of a university thanks to the determination of one or two people who subsequently transformed the life of an entire university, such as that ofDar es Salaam, Tanzania. does it not invite us to think and to believe that there is hope?
Keywords: African Research